Unpublished letter from Professor F. P. Fedorov about the historical prose of the Russian Diaspora - Pavel Glushakov (Literatūra (Vilnius))
A letter by Professor F. Fedorov is published, in which he speaks in detail about a dissertation nresearch devoted to historical prose in the literature of emigration. The letter is of interest not only as a sign of the scientist’s attention to the work of a young colleague, but also for those reflections that are a deep analytical analysis of the topic of historical prose in the literature of the Russian Diaspora. In fact, this text is a completely independent statement of a scientist on a topic that has not yet been fully clarified in literary science. Broad generalizations and valuable conclusions make this letter an important fact not only in maintaining the memory of the deceased researcher, but also outline promising ways for studying the literature of emigration in Latvia.